Mood and anxiety disorders in patients with abnormal uterine bleeding. (April 2016) - Kayhan, Fatih; Alptekin, Hüsnü; Kayhan, Ayşegül
Abstract: Objective: We aimed to investigate the prevalence of mood and anxiety disorders in patients with abnormal uterine bleeding (AUB) and the relationship between mood and anxiety disorders and AUB. Method: 96 consecutive patients with not yet classified AUB based on the PALM-COEIN classification and 94 volunteers were included in the study. Mood and anxiety disorders were ascertained by means of the Structured Clinical Interview for the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition/Clinical Version. Results: Out of 96 patients, 55 (57.3%) met the criteria for at least one diagnosis of mood and anxiety disorder. The most common psychiatric disorders in patients with AUB were major depression ( n  = 15, 15.6%), generalized anxiety disorder ( n  = 18, 18.8%) and obsessive compulsive disorder ( n  = 22, 22.9%), respectively. Compared with the control group, the prevalence of any psychiatric disorder ( x 2  =  43.52, p =  0.000), any mood disorder ( x 2  =  10:37, p =  0.001) and any anxiety disorder ( Fisher's exact test, p =  0.000) was higher in patients with AUB. The presence of any mood and anxiety disorder was an independent risk factor for AUB. Conclusion: Mood and anxiety disorders, particularly major depression, generalized anxiety disorder and obsessive-compulsive disorder were frequently observed in patients with AUB.